Pengaruh Pembelajaran Online Berbasis e-Learning melalui Aplikasi Zenius terhadap Hasil Belajar Siswa SMA - Mansur, Muhammad Yogi Zifari; Sukarno, Gendut (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Students can obtain lessons outside of school through educational startups such as Zenius, Quipper, and Ruangguru. Learning courses that were previously done conventionally (face-to-face or offline) can now be done online with applications like Zenius. This study aims to evaluate the effect of e-Learning learning methods on high school student learning outcomes. Data was collected through questionnaires and analyzed with a discrepancy evaluation model. Application success is measured by absolute criteria. Respondents in this study are high school students consisting of grades 7, 8, and 9, both directly and indirectly involved with the Zenius application. With 53.3% of students stating neutral towards the influence of the Zenius application, it can be concluded that the application does not have a significant impact on the learning outcomes of the respondents.